Exploring parents’ beliefs toward children’s English learning in a multilingual Tenggerese community - Laras Asihing Tyas; Nurenzia Yannuar; Evynurul Laily Zen (University of Muhammadiyah Malang, 2025)
Parents’ beliefs significantly influence how children experience and engage with language learning, especially in multilingual settings where local and global languages coexist. This study examines how Tenggerese parents understand and respond to their children’s English learning within an informal language course context. Situated in Tosari Village, Bromo, East Java, an indigenous and multilingual community, the research seeks to capture parental perspectives on English education amid ongoing cultural and linguistic diversity. Adopting a qualitative case study approach, semi-structured interviews were conducted with six parents whose children attend a local English course. The thematic analysis identified three central patterns: parents’ generally positive views of English and its perceived relevance for education, tourism, and global interaction; their conscious efforts to support English learning while maintaining Tenggerese language and cultural traditions; and differing forms of parental involvement shaped by socioeconomic conditions and educational backgrounds. Although many parents had limited English proficiency, they showed strong emotional commitment and viewed English as an additional resource rather than a replacement for their local language. These findings illustrate how indigenous parents engage in adaptive multilingual practices that connect global aspirations with cultural continuity. The study adds to existing discussions on parental beliefs in EFL contexts and offers insights for developing culturally responsive English education in rural and indigenous settings.